The four 18th century streams on productive labour - Perrotta, Cosimo (Iberian Journal of the History of Economic Thought, 2015)
This article first recalls our previous research on the original approach on productive labour, which goes from Petty to Genovesi (1767). That approach, being mainly empirical, divided jobs into more or less productive. The other most important approaches came later: Quesnay founded productive labour on surplus, Condillac on utility, Smith on exchange value. All of them gave the concept a more rigorous, but also more rigid shape: jobs were divided into productive or unproductive once and for all. Moreover social utility and productive nature of labour became separated qualities. Smith’s concern was to fight the waste of the aristocrats, which fed unproductive labour and subtracted resources from investment and productive labour. But for Smith public services and intellectual labour are unproduc-tive because their product is not material. So, he puts the seeds of the dissolution of his own theory. The following decades witness a confrontation between the physiocratic and the Smithian approach. In the end the latter prevails, but its inconsistencies emerge.